Combined Effect of Environmental Factors on Spoilage Bacteria - Chandrasekharan, M.; Lakshmanaperumalsamy, P.; Chandramohan, D. (Fishery Technology, 2025)
Effect of environmental factors such as temperature,pH and sodium chloride concentrations, individually and at various combinations, on the growth and survival of spoilage bacteria was studied in flesh broth and Zobells broth. Eight isolates, belonging to three different genera namely, Pseudomonas, Vibrio and Acinetobacter, harvested from spoiled Penaeus indicus were stored at 5,15,30,35 and 50Â°C, pH 2,4,6,8,10 and 12 and sodium chloride concentrations of 0,1,3,6,10 and 15%. Optimum growth for all the isolates was found to vary from 15 to 45Â°C and pH from 5-10. The growth pattern of all the isolates, in rcsponse to various sodium chloride concentrations was not similar in flesh broth and Zobells broth. Optimum sodium chloride concentration was found to vary from 1 to 6%. Influence of more than one environmental factor on the growth of spoilage bacteria was tested at various levels in flesh media by maintaining one of the factors constant and altering the other two. Results suggested that at extreme conditions each individual factor had an independent influence on the growth of bacteria.